GUARDIAN'S RESPONSIBILITY FOR THE WELFARE OF CHILDREN IN MARRIAGE: A STUDY ACCORDING TO ISLAMIC LAW - Redwan Yasin; Nurul Hidayat Abdul Rahman; Sayuti Ab. Ghani; Mohamed Belal (Malaysian Journal of Syariah and Law)
In Islam, guardianship is a fundamental pillar of marriage, particularly in cases involving children, highlighting the guardian's critical role in ensuring the child's welfare is fully protected before the marriage is solemnised. This responsibility is essential in preventing potential child abuse arising from the guardian's failure to safeguard the child's rights adequately. This article seeks to elucidate the Islamic legal concept of guardianship in marriage and the guardian's duty to ensure the well-being of children born within the marital union. The analysis extends to key aspects of child welfare that require careful consideration before entering marriage. The research methodology follows a content analysis approach, thoroughly examining textual and contextual elements within Islamic legal sources, scholarly writings, and relevant documents. The research is based on two primary theoretical frameworks, namely Maqasid al-Shari’ah, which provides a comprehensive understanding of how guardianship aligns with the broader objectives of Shari’ah, and Fiqh, which offers a detailed exploration of specific legal rulings across various schools of thought. The findings highlight that, despite the guardian's inherent discretion in facilitating a marriage, Islamic law obliges the guardian to prioritise and take responsibility for the child's welfare. This obligation stems from the understanding that, by overseeing the marriage, the guardian is also accountable for protecting the child from harm throughout the marital period. This study contributes to the scholarly discourse on Islamic family law, providing insights into the theoretical foundations and practical implications of guardianship and child welfare within Islamic marriages.